Three methods for inoculation of viral vectors into plants - Monroy-Borrego, Andrea G.; Steinmetz, Nicole F. (Frontiers in Plant Science, 2022)
Agriculture is facing new challenges every day, with global warming modifying the survival chances for crops, and new pests on the horizon. To keep up with these challenges, gene delivery provides tools increase crop yields. On the other hand, gene delivery also opens the door for molecular farming of pharmaceuticals in plants. However toward increased food production and scalable molecular farming, there remain technical difficulties and regulatory hurdles to overcome. Transient genetic delivery offers an alternative to traditional genetic engineering and can bypass GMO regulations and therefore is a desired method and utilizes Agrobacterium tumefaciens, viral vectors and other nanoparticle-based delivery strategies. In this work, we used the tobacco mosaic virus (TMV) as a model system. TMV is widely used for a viral vector and nanoparticle platform used in vaccine design and drug delivery. We studied the effectiveness of three inoculation techniques: mechanical inoculation, Silwet-77 foliar spray and petiole injections. While mechanical vs. Silwet-77 foliar spray have already been reported, inoculation making use of needle-laden syringe to target and inject the viral vector into the vasculature of the plant is a novel approach. All methods were successful and TMV infection was established at overall comparable yields. Each method has its advantages: while spray application is highly scalable application and may find application for farming, the syringe inoculation could provide a clean aseptic controlled approach for molecular farming of pharmaceuticals under good manufacturing protocols (GMP) and would even be applicable for gene delivery to plants in space.